Issues facing implementation of biological control in the tropics - Greathead, D.J. (International Inst. of Biological Control (IIBC), Silwood Park, Acot, Berks, Sl5 7TA (United Kingdom)) (Malaysian Plant Protection Society, 2013)
Examination of past biological control programmes worldwide shows that outstanding successes are the best promoters of biological control and also that the possibility of success is increased when programmes are scientifically planned and adequately funded. Thus, several recent successful programmes of major importance to tropical agriculture have stimulated interest in tropical countries and led to the initiation of other biological control programmes. At the same time increasing concern over the use of toxic chemical pesticides is encouraging scientists and agriculturists to adopt pest management programmes in which biological control has a central role. Thus, there is now an unprecedented opportunity to promote biological control methods. However, increased activity has drawn the attention of administrators and regulatory bodies to biological control and has raised public concern over the consequences of releasing exotic organisms into the environment. Therefore, it is necessary for biological control practitioners to ensure that they explain the scientific basis for their work and to allay unnecessary fears. It is also necessary that they provide guidance to legislators so as to encourage the adoption of rational protocols to facilitate biological control and ensure that it is undertaken responsibly. Biological control is underfunded compared with other major components of pest management, notably plant breeding and pesticides. Thus, increased financial support is required to expand research and coordinate scattered resources at international, regional and national levels so as to improve its effectiveness and to promote its use in sustainable biologically sound pest management. It is also essential that extension personnel and farmers understand the benefits of biological control so that they will adopt pest management programmes and urge their governments to support its implementation